A review on the potential biotechnological applications of the operational group Bacillus amyloliquefaciens - Ngalimat, Mohamad Syazwan; Radin Yahaya, Radin Shafierul; Al-adil Baharudin, Mohamad Malik; Mohd Yaminudin, Syafiqah; Karim, Murni; Ahmad, Siti Aqlima; Sabri, Suriana (Multidisciplinary Digital Publishing Institute, 2021)
Bacteria under the operational group Bacillus amyloliquefaciens (OGBa) are all Gram-positive, endospore-forming, and rod-shaped. Taxonomically, the OGBa belongs to the Bacillus subtilis species complex, family Bacillaceae, class Bacilli, and phylum Firmicutes. To date, the OGBa comprises four bacterial species: Bacillus amyloliquefaciens, Bacillus siamensis, Bacillus velezensis and Bacillus nakamurai. They are widely distributed in various niches including soil, plants, food, and water. A resurgence in genome mining has caused an increased focus on the biotechnological applications of bacterial species belonging to the OGBa. The members of OGBa are known as plant growth-promoting bacteria (PGPB) due to their abilities to fix nitrogen, solubilize phosphate, and produce siderophore and phytohormones, as well as antimicrobial compounds. Moreover, they are also reported to produce various enzymes including α-amylase, protease, lipase, cellulase, xylanase, pectinase, aminotransferase, barnase, peroxidase, and laccase. Antimicrobial compounds that able to inhibit the growth of pathogens including non-ribosomal peptides and polyketides are also produced by these bacteria. Within the OGBa, various B. velezensis strains are promising for use as probiotics for animals and fishes. Genome mining has revealed the potential applications of members of OGBa for removing organophosphorus (OPs) pesticides. Thus, this review focused on the applicability of members of OGBa as plant growth promoters, biocontrol agents, probiotics, bioremediation agents, as well as producers of commercial enzymes and antibiotics. Here, the bioformulations and commercial products available based on these bacteria are also highlighted. This review will better facilitate understandings of members of OGBa and their biotechnological applications.